Analisis Data Gravitasi Untuk Identifikasi Struktur Bawah Permukaan Daerah Potensi Panas Bumi Cipari - Ninik Agustin; Agung Wibawa (Universitas Negeri Gorontalo, 2022)
Geothermal prospect in Cipari has been shown by spring who has a temperature of about 50°C and is categorized as a low temperature. The presence of spring on Cipari earth's surface is an indication of geothermal structures' existence on the surface and a geothermal system below the surface. Geophysical methods can be used for subsurface structures identification, one of them is the density method with gravity data. This study has an objective to identify the subsurface structures in Cipari geothermal potential area using GGMPlus gravity data. Terrain and Bouguer corrections were used to obtain Complete Bouguer Anomaly (CBA). Separation of regional and residual anomalies using Butterwoth and Bandpass filters. The rock contact boundary was obtained by the FHD method and geological structures such as faults were obtained by the SVD method. FHD and SVD results were used as information for 2D forward modeling. The ABL map shows anomalous contrasts in areas that have rock contacts and geological faults. The high anomaly in the center of the study area indicates the Cipari anticline. Data processing and analysis concluded that the area around the Cipari hot spring has anticline, several rock contacts, and normal fault structures. The fault in the study area is part of the geothermal system which is confirmed by GGMPlus data.